PENGEMBANGAN PARIWISATA OLAHRAGA UNTUK MENINGKATKAN PELUANG KERJA DI ERA EKONOMI KREATIF DI SULAWESI UTARA - Lagarense, Bet El SIlisna; Walansendow, Agustinus; Lagarense, Jeskrispen (Jurnal Ilmu Pariwisata, 2025)
Sport tourism is an alternative tourism model with significant potential to drive economic growth andjob creation, especially in the era of the creative economy. This study aims to identify the potentials,challenges, and development strategies of sport tourism to enhance employment opportunities in thetourism sector and local economies. A descriptive-qualitative approach was employed, utilizingliterature studies, field observations, and interviews with tourism actors, sports communities, and localstakeholders. The results indicate that sport tourism can generate a variety of direct and indirect jobopportunities, including sports guides, event organizers, fitness instructors, and supporting MSMEs inNorth Sulawesi. Therefore, collaboration among stakeholders, infrastructure development, and humanresource training oriented toward the integration of sports, tourism, and creative innovation areessential. This study concludes that developing sport tourism is a relevant and sustainable strategy tosupport the creative economy and broaden employment access at both local and national levels